Interview with Prof. Akira Matsumura: the accelerator-based clinical trial of BNCT for melanoma will be started in 2019 - Fan, Wei-En (Therapeutic Radiology and Oncology, 2018)
The 18th International Congress on Neutron Capture Therapy (ICNCT) was successfully held in Taipei, Taiwan from October 28 to November 2. Researchers came from different countries, such as Japan, USA, Italy, Argentina, Germany, Finland, etc. to attend this grand meeting. The gathering of researchers in the fields of radiology, chemistry, physics, nuclear medicine and pathology has enriched and stimulated discussion during the meeting. AME editorial team had the honor to interview Prof. Akira Matsumura from the University of Tsukuba. Prof. Matsumura gave a speech on “Current status of i-BNCT project at Tsukuba & Tokai”. Through his speech, we learned that his team is already performing preclinical trail for malignant melanoma and will conduct phase I clinical trial in the coming year.